1993
DOI: 10.1021/j100137a029
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of n-octane confined between parallel solid surfaces: structure and adhesive forces vs film thickness from molecular dynamics simulations

Abstract: Molecular fluids in confined spaces exhibit behavior that cannot be properly described by continuum theories. We examine the structure of n-octane confined between crystalline surfaces and in equilibrium with the bulk liquid at 1 atm and 297 K using molecular dynamics simulations of a chemically realistic model of the molecules.We also compute the solvation forces acting upon the surfaces as a function of their separation. The films are studied between solid surfaces separated by gaps of 1 .O-2.4 nm. At 297 K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
(17 reference statements)
1
12
0
Order By: Relevance
“…On the contrary, the molecules reportedly collapse into compact configurations. Wang et al 24 in their equilibrium simulation of noctane using a model similar to the one used in our study, also report the films retaining diffusive and conformational properties resembling a liquid even though strong layering in the films is observed. Experimental studies on squalane by Reiter et al 25 show that molecular thin liquid films of alkanes in the elastic rest state are very different from solids in the bulk; they are much weaker and more deformable than a molecular crystal or glass, which is in contrast to the beadspring simulation results.…”
Section: Discussionsupporting
confidence: 70%
“…On the contrary, the molecules reportedly collapse into compact configurations. Wang et al 24 in their equilibrium simulation of noctane using a model similar to the one used in our study, also report the films retaining diffusive and conformational properties resembling a liquid even though strong layering in the films is observed. Experimental studies on squalane by Reiter et al 25 show that molecular thin liquid films of alkanes in the elastic rest state are very different from solids in the bulk; they are much weaker and more deformable than a molecular crystal or glass, which is in contrast to the beadspring simulation results.…”
Section: Discussionsupporting
confidence: 70%
“…The oscillating solvation force provides evidence of a strongly layered structure and a solid-like response when the mica separations become as small as a few methylene diameters. Concurrent computer modeling studies [2][3][4][5][6][7][8][9] have captured this macroscopic response of the normal force and have at the same time unveiled clearly layered density profiles normal to the confining surfaces. In addition, the computer studies revealed details such as a strong inhomogeneity of dynamics across the slit and dramatic increases of relaxation times near strongly physisorbing surfaces.…”
Section: Introductionmentioning
confidence: 95%
“…This information is of fundamental and practical importance and would greatly contribute to a deeper understanding of the behavior of fluids in the vicinity of confining surfaces, 16 as well as provide insight for material design for many applications. 14 Although many molecular dynamics and Monte Carlo simulations have been employed to study confined thin films of alkanes and alkanes at fluid-surface interfaces, [3][4][5][6][7][8][9] there are far fewer studies of grafted alkane oligomers. [17][18][19] Due to the extremely high grafting densities used in the latter studies, their results are not applicable to the systems of interest here.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations of interfacial liquid junctions and confined films have been carried out to understand the physical properties and response of model lubricants and their molecular characteristics, such as chain length and molecular structure (for example, straight versus branched chains) (Thompson and Robbins, 1990a, b;Robbins and Thompson, 1991;Ribarsky and Landman, 1992;Thompson et al, 1992;Landman et al, 1993;Wang et al, 1993;Bhushan et al, 1995a;. The confinement of n-octane ranging in thickness from 1 to 2.4 nm, between parallel, crystalline solid walls (rigid Langmuir-Blodgett layers), was studied by Wang et al (1993).…”
Section: Interfacial Liquid Junctions and Confined Filmsmentioning
confidence: 99%